The Influence of Education Level and Competence on The Performance of Information and Documentation Manage-Ment Officials (PPID) Within The Government of Ogan Komering Ulu District - Fitriany, Diana; Sari, Yunita; Oktarina, Yetty (Jurnal Manajemen STIE Muhammadiyah Palopo, 2024)
Abstract This study aims to determine the effect of education level (X1) and competence (X2) on the performance of Information and Documentation Management Officials (PPID) in Ogan Komering Ulu Regency. Using multiple linear regression, the research involved a population of 49 PPID officers. The findings indicate that both education level (X1) and competence (X2) significantly affect performance, with competence exhibiting a stronger influence (coefficient 0.785) compared to education (coefficient 0.241). Together, these factors explain 58.6% of performance variability, while 41.4% is attributed to other variables. Recommendations include targeted training programs, enhanced recruitment criteria emphasizing competencies, and policies fostering continuous education. This study offers insights for regional governments to optimize PPID performance, ensuring efficient public information management.Keywords: Education Level, Competence, PPID Performance, Regional Government, Public Information Management